Coenzyme Q10 Supplementation Improves Ovarian Function and Folliculogenesis in Women Undergoing In Vitro Fertilization - Mengying, Li; Liu, Yang; Lan, Liu; Lan, Liu (Current topics in nutraceuticals research, 2024)
Coenzyme Q10 plays a critical role in cellular energy production and antioxidative processes within mitochondria. This study aimed to evaluate the impact of coenzyme Q10 supplementation on in vitro fertilization outcomes, focusing on antral follicle count, retrieved oocytes, quality of oocytes, fertilization rate, and implantation rate. The study included 270 women undergoing in vitro fertilization treatment, each receiving 200 mg of coenzyme Q10 daily for 60 days before and throughout the in vitro fertilization cycle. Other key nutritional supplements taken by participants included folic acid, vitamin D, omega-3, multivitamins, and probiotics. Coenzyme Q10 supplementation was positively correlated with several in vitro fertilization outcomes. The mean antral follicle count was 12.8, with a positive correlation of 0.35 with the use of coenzyme Q10. The mean number of retrieved oocytes was 9.7, showing a positive correlation of 0.30 with coenzyme Q10. The quality of oocytes had a weaker correlation of 0.20 with coenzyme Q10. Fertilization rate and implantation rate had positive correlations of 0.15 and 0.10, respectively. Additional supplements, such as folic acid and multivitamins, were used by a high percentage of participants, indicating the broader role of nutritional support in in vitro fertilization treatment. Coenzyme Q10 supplementation appears to positively impact several in vitro fertilization outcomes, suggesting its potential as a beneficial adjunct to standard in vitro fertilization protocols.